2001
DOI: 10.1017/s1461145701002280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluoxetine on regional cerebral metabolism in autistic spectrum disorders: a pilot study

Abstract: The regional metabolic effects of fluoxetine were examined in patients with autism spectrum disorders. Six adult patients with DSM-IV and Autism Diagnostic Interview (ADI) diagnoses of autism (n l 5) and Asperger's syndrome (n l 1), entered a 16-wk placebo-controlled cross-over trial of fluoxetine. The patients received ")F-deoxyglucose positron emission tomography with co-registered magnetic resonance imaging at baseline and at the end of the period of fluoxetine administration. After treatment, the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 24 publications
4
56
0
3
Order By: Relevance
“…Such a pattern of disturbance would correspond to the low left-hemisphere serotonin found with C 11 -AMT PET scans in young boys with autism (Chugani et al 1997, DeLong 1999. Recently, it has been found that fluoxetine treatment increases regional cerebral glucose metabolism as shown by F 18 DG PET (18-fluorodeoxyglucose positron emission tomography) studies in autistic patients (Buchsbaum et al 2001). …”
Section: Discussionmentioning
confidence: 70%
“…Such a pattern of disturbance would correspond to the low left-hemisphere serotonin found with C 11 -AMT PET scans in young boys with autism (Chugani et al 1997, DeLong 1999. Recently, it has been found that fluoxetine treatment increases regional cerebral glucose metabolism as shown by F 18 DG PET (18-fluorodeoxyglucose positron emission tomography) studies in autistic patients (Buchsbaum et al 2001). …”
Section: Discussionmentioning
confidence: 70%
“…RCTs treating OCD symptoms among participants with ASD, 11 studies (Hollander et al 2005(Hollander et al , 2006aKing et al 2009;Martin et al 1999Martin et al , 2003McDougle et al 1997McDougle et al , 2000McDougle et al , 2005Posey et al 2007;Stigler et al 2009) evaluated interventions for children and adolescents (<18 years), 6 studies (McDougle et al 1995a(McDougle et al , 1996(McDougle et al , 1998Buchsbaum et al 2001;Hollander et al 2003Hollander et al , 2012 evaluated treatment for adults, and 2 studies (Gordon et al 1993;Potenza et al 1999) included both children and adults. None included participants with a formal diagnosis of OCD.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…We assessed rGMR within BAs by tracing coronal slices based on a digitized brain atlas with 33 coronal slice maps of BAs defined by microscopic examination of an entire postmortem brain, a technique detailed elsewhere (Buchsbaum et al, 2001Hazlett et al, 2000;Mitelman et al, 2005). To assess the effect of m-CPP on rGMR, the dependent measure for PET analyses on drug effect was expressed as difference scores (m-CPP-placebo) for rGMR within each BA, calculated by subtracting placebo counts for each region of interest in each subject from the corresponding rGMR from the m-CPP scan.…”
Section: Regions Of Interest Approachmentioning
confidence: 99%